Rodnost, etničnost in nacija - Knežević Hočevar, Duška (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2006)
Since 2000, the discussion on population implosion - sustained below replacement level fertility - in the developed world has prevailed over the previous demographic concern about the population explosion in the developing world. European governments seek to solve repercussions of such population trend, particularly the ageing society,by two scenarios: by pro-natalist measures or by immigration. The latter seems controversial in view of hot public debates on the loss of national identity, and the fear of discrimination or xenophobia outbursts usually underlies such discussions. Moreover, the European states do not perceive themselves as immigrant societies. The death of the nation and similar metaphors implicitly presume who should reproduce, instead of recognizing the legitimacy of those who actually do. It is not so much that the European states are sterile, but that certain understandings of nation are in increasing inconsistency with the demographic reality. Therefore, the study of population dynamics can no longer be separated from the study of ethnicity, nationalism and international affairs; it is also necessary to re-consider the still prevailing statistical realism . The understanding of sustained fertility below replacement level will be much better if grounded in alternative demographies that clarify the general trends of population dynamics through individual experiences.
Keywords: rodnost; etničnost; narod; people; narodna identiteta; Europe; Evropa